THE DEVELOPMENTOF ARGUMENTATIVE ASSESSMENT TO IMPROVE THE DISCOURSE PATTERNIN STUDENTâS ARGUMENTATION ON THE CONCEPT OF HUMAN PHYSIOLOGY - Roshayanti, Fenny; Rustaman, Nuryani Y. (BIOMA, 2013)
A study with R & D method focusing on improving the skills of arguing in the concept of human physiology was conducted through the development of model of Assessment Argumentative. The model was outlined in the form of argumentation observation sheet(LOAKp). A number of sixth semester students of Biology Education attending subject of Human Physiology (n=121) were involved as research subject. The implementation study applied Research and Development design. TAP (Toulmin Argumentation Pattern) comprising components of claim, warrant, backing and rebuttal had been used to analyze argumentation discourse. Arguing skills were qualitatively and quantitatively measured by complexity of argumentation pattern (PWArKp). The instrument of assessment argumentative model as observation sheet of argumentation discourse which had been implemented through stages (scaffolding) with particular standpoints. The results show that the aspects of PWArKp are generally developed from the early stages to the final stage. However, complexity of argumentationdiscourse still need to be improved because some standpoints have responed on level 1 or leve 2. Thus skills of arguing of students in complexity of argumentation pattern aspects need further in depth study by providing students more opportunities to engage in argumentative discourse.Key words: Assessment Arguementative, argumentation skill, human physiology concepts